Growth policy in a small, open economy. Domestic innovation and learning from abroad - Brita Bye; Taran Fæhn; Leo A. Grünfeld (Statistics Norway, Research Department, 2008)
Research and development (R&D) play a pivotal role for innovation and productivity growth, and knowledge spillovers can make the case for public support to private R&D. In small and open economies, absorption of foreign knowledge through exports and imports can be even more decisive for economic growth than domestic innovation. This macro economic analysis investigates how policies should be formed in order to reap the largest productivity effects, when both these sources of growth interplay. In particular, the firms' capacity to absorb knowledge from abroad depends on domestic R&D, and this reinforces the efficiency arguments for stimulating R&D. We find that from a welfare perspective, export promotion of R&D-based technologies proves slightly more efficient than R&D support.
Keywords: 330; Absorptive capacity; Computable general equilibrium model; Endogenous growth; Research and Development; Spillovers; Two faces of R&D.